Cerebral autoregulation and cerebral blood flow response to mean arterial pressure challenge following induction of general anaesthesia for neuroradiology procedure - Manquat, Elsa; Ravaux, Hugues; Souilamas, Jihane; Chamoux, Thibaut; Joaquim, Jona; Gayat, Etienne; Vallée, Fabrice; Cartailler, Jérôme (Frontiers in Anesthesiology, 2023)
Introduction Intraoperative hypotension is common following general anaesthesia induction with propofol, but its impact on cerebral autoregulation (CA) remains unclear. We investigate the incidence and risk factors of impaired CApost-propofol induction and its recovery after a mean arterial pressure (mAP) challenge. Methods We included 40 non-emergency neuroradiology surgery patients [58 (47, 58)years old., 57% women]. We recorded mAP, mean blood flow velocity in the mean cerebral artery (MCAvmean), and regional cerebral oxygen saturation (rSO2). We computed the mean flow index (Mxa) pre and post mAP challenge. Mxa > 0.3 defined poor CA. Results After anaesthesia induction, 21 (53%) had impaired CBF autoregulation (CA−, Mxa > 0.3). The average mAP was 66 ± 9 mmHg, average MCAv was 39 ± 12 cm.s−1, and rSO2 was 63 ± 7%. We found no significant difference in age, norepinephrine infusion rate, and cardiovascular risks factors were similar between CA− and CA+ (Mxa ≤ 0.3) patients. Among the 22 patients (CA−: n = 14; CA+: n = 8) undergoing mAP challenge, there was a significant Mxa improvement and MCAv increase among CA− patients, (CA−: 0.63 ± 0.18 vs. 0.28 ± 0.20, p < 0.001), and [absolute variation: 1 (0.7–1.5) vs. 7 (3–9) cm.sec−1], respectively. Conclusion After induction of general anaesthesia for neuroradiology procedure, 53% of the patients had an impaired CA, regardless of age or medical history. Importantly, a mAP challenge effectively restored CA and improved CBF. Clinical Trial Registration identifier, NCT04288869